2019
DOI: 10.1108/jcs-05-2018-0010
|View full text |Cite
|
Sign up to set email alerts
|

Let’s talk about adaptation! How individuals discuss adaptation during evidence-based practice implementation

Abstract: Purpose Researchers suggest that adaptation should be a planned process, with practitioners actively consulting with program developers or academic partners, but few studies have examined how adaptation unfolds during evidence-based practice (EBP) implementation. The purpose of this paper is to describe real-world adaptation discussions and the conditions under which they occurred during the implementation of a new practice across multiple county child welfare systems. Design/methodology/approach This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
(50 reference statements)
1
3
0
Order By: Relevance
“…Our findings showed that implementation champions and managers made both planned adaptations and haphazard modifications to better fit the content and context. This finding is in line with previous studies, which have reported both adaptations and modifications to EBIs [ 8 , 9 , 64 66 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings showed that implementation champions and managers made both planned adaptations and haphazard modifications to better fit the content and context. This finding is in line with previous studies, which have reported both adaptations and modifications to EBIs [ 8 , 9 , 64 66 ].…”
Section: Discussionsupporting
confidence: 93%
“…Adaptations to EBIs challenge the basic assumption that the core components of an intervention must be implemented with fidelity to achieve its intended effectiveness and expected outcomes [ 8 – 10 ]. Much of the fidelity versus adaptation debate has been theoretical [ 1 ], but Durlak [ 11 ] has estimated that as much as 80% of an EBI’s prescribed activities may be omitted during implementation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations